Malignant cell characterization via mathematical analysis of bio impedance and optical properties. (2nd January 2021) - Hossain, Shadeeb
ABSTRACT: Diagnosis in the early stage of breast cancer is crucial for the onset of preliminary treatment. Non-radiative bioimpedance measurement in the microwave frequency range can contribute to electrode-medium interface error and the malaise of electrode placement on the patient to take measurements. These reasons account for alternate diagnosis procedure and improved reliability of retrieved mensuration. Non-invasive optical diagnosis in the near infra-red (NIR) and visible light of the electromagnetic range is the shifting paradigm for healthcare diagnosis. An accurate quantitative measurement is unparalleled to circumvent false positives. The focus of this paper is to perform quantitative mathematical analysis for bioimpedance and optical properties for sample breast cancer cells for meticulous interpretation of malignant cell diagnosis. The analytical solution of the Cole–Cole plot, relaxation frequency, and capacitance measurement showed reliability with previous experimental findings. The dissimilitude of the frequency-dependent refractive index measurement of the malignant and healthy cell can be used by clinicians for pronouncement. The diffusion theory is also used to interpret the pathlength of the source light particle and the absorption property of the malignant cell. The synergistic analytical solutions of the bioimpedance and optical parameters can be used by licensed Physicians or Clinical Practitioners (CP) to meticulously interpret the diagnosis result. The quantitative parameters obtained from the dispersed bandwidth range from microwave to visible light offers a comprehensive understanding of the biophysical properties of the malignant cell.